2020
DOI: 10.3390/jcm9113590
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Disease and Ocular Comorbidity Analysis of Geographically Isolated Federally Recognized American Indian Tribes of the Intermountain West

Abstract: Background: The American Indian Navajo and Goshute peoples are underserved patient populations residing in the Four Corners area of the United States and Ibupah, Utah, respectively. Methods: We conducted a cross-sectional study of epidemiological factors and lipid biomarkers that may be associated with type II diabetes, hypertension and retinal manifestations in tribal and non-tribal members in the study areas (n = 146 participants). We performed multivariate analyses to determine which, if any, risk factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…In this multivariate analysis, we found that both iStent (p < 0.0001) and the number of medications pre-operation (p < 0.001) were statistically associated with the outcome of medication reduction at p < 0.05 (Table 6). We then completed a multivariate analysis with all of the variables of interest, including, age, gender, race/ethnicity, iStent, and pre-SLT IOP [35][36][37][38][39][40]. We found that in the complete multivariate analysis only the initial IOP pre-operation (p < 0.0001) was statistically associated with the outcome of percent IOP reduction post-SLT at p < 0.05 (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…In this multivariate analysis, we found that both iStent (p < 0.0001) and the number of medications pre-operation (p < 0.001) were statistically associated with the outcome of medication reduction at p < 0.05 (Table 6). We then completed a multivariate analysis with all of the variables of interest, including, age, gender, race/ethnicity, iStent, and pre-SLT IOP [35][36][37][38][39][40]. We found that in the complete multivariate analysis only the initial IOP pre-operation (p < 0.0001) was statistically associated with the outcome of percent IOP reduction post-SLT at p < 0.05 (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Rural, isolated populations, even with a small study sample size, are essential populations to include in research, because if they are ignored, health disparities will only further increase [ 90 , 105 ]. Future research is needed to validate the genetic findings based on leukocyte DNA from blood.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not exclusively observe different Maya cultural groups; therefore, future studies may identify specific wants and needs pertaining to eye health and eye research within the more than 20 different Guatemala Mayan communities that differ by both language and culture [ 156 ]. Our previous research within the American Indian tribes of the Intermountain West has shown that there are differences in the prevalence of blinding eye disease within the same state at the tribal level; therefore, this research is essential to determine differences that may occur between Mayan communities in Guatemala [ 90 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations